Reduced Neuronal Transcription of Escargot, the Drosophila Gene Encoding a Snail-Type Transcription Factor, Promotes Longevity - Symonenko, Alexander V.; Roshina, Natalia V.; Krementsova, Anna V.; Pasyukova, Elena G. (Frontiers in Genetics, 2018)
In recent years, several genes involved in complex neuron specification networks have been shown to control life span. However, information on these genes is scattered, and studies to discover new neuronal genes and gene cascades contributing to life span control are needed, especially because of the recognized role of the nervous system in governing homeostasis, aging and longevity. Previously, we demonstrated that several genes that encode RNA polymerase II transcription factors and that are involved in the development of the nervous system affect life span in Drosophila melanogaster. Among other genes, escargot (esg) was demonstrated to be causally associated with an increase in the life span of male flies. Here, we present new data on the role of esg in life span control. We show that esg affects the life spans of both mated and unmated males and females to varying degrees. By analyzing the survival and locomotion of the esg mutants, we demonstrate that esg is involved in the control of aging and that increased longevity is caused by decreased esg transcription. In particular, we demonstrate that esg knockdown in the nervous system increased life span, directly establishing the involvement of the neuronal esg function in life span control. Our data invite attention to the mechanisms regulating the esg transcription rate, which is changed by insertions of DNA fragments of different sizes downstream of the structural part of the gene, indicating the direction of further research. Our data agree with the previously made suggestion that alterations in gene expression during development might affect adult lifespan, due to epigenetic patterns inherited in cell lineages or predetermined during the development of the structural and functional properties of the nervous system.